2019
DOI: 10.1136/ijgc-2019-000343
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for spontaneous regression of high-risk human papillomavirus-positive cervical intra-epithelial neoplasia grade 2

Abstract: IntroductionSince the implementation of human papillomavirus (HPV)-based screening for cervical cancer, the majority of cervical intra-epithelial neoplasia grade 2 (CIN2) lesions are high-risk (hr)HPV positive. Evidence on prognostic factors in hrHPV-positive CIN2 is lacking, hampering the individual counseling of women undergoing observation as routine management. The aim of this study is to identify prognostic factors for the spontaneous regression of hrHPV-positive CIN2.MethodsA retrospective cohort study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
(17 reference statements)
1
10
0
2
Order By: Relevance
“…Clinicopathological factors including HPV genotype, tobacco smoking, hormonal contraceptives, socioeconomic aspects, reproductive, and sexual factors have been reported as significant for CIN development [ 63 , 64 , 65 , 66 ]. Yet, only a few studies have investigated potential prognostic markers for CIN regression, and predictive power have been identified for HPV genotype [ 67 ], microbiota [ 68 ], age [ 69 ], parity, and smoking status [ 70 ]. CIN2 is known to have a higher probability of regression, and whether conservative treatment should be recommended for these patients is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathological factors including HPV genotype, tobacco smoking, hormonal contraceptives, socioeconomic aspects, reproductive, and sexual factors have been reported as significant for CIN development [ 63 , 64 , 65 , 66 ]. Yet, only a few studies have investigated potential prognostic markers for CIN regression, and predictive power have been identified for HPV genotype [ 67 ], microbiota [ 68 ], age [ 69 ], parity, and smoking status [ 70 ]. CIN2 is known to have a higher probability of regression, and whether conservative treatment should be recommended for these patients is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…This effect might be mediated by lower repetitively exposure of the cervical tissue to HPV and semen, which has an immunosuppressive effect [ 118 ]. Lastly, nulliparous women with cHSIL have a 5 times greater likelihood of spontaneous regression than parous women [ 119 ]. This might be explained by increased hormone levels and weakened immune response during pregnancy and tissue damage of the cervix during vaginal delivery [ 120 , 121 ].…”
Section: Importance Of Clinical Parameters and Hpv Genotype In The Na...mentioning
confidence: 99%
“…Further, several systematic reviews have shown that cytological smears are predictive of high-grade cervical lesions (HSIL/HSIL+). [9,15,16] Hence, post-treatment cytology smears and HPV testing are critical, regardless of the treatment modality, especially in older women whose age over 50 years old. Xiao Li et al suggested that postmenopausal patients with high-grade squamous intermediately lesions should be treated preferentially with cold knife conization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, factors like smoking status, which affects the regression of CIN2 lesions in high-risk HPV-positive patients, were not regarded as. [16] Furthermore, the follow-up period was not long enough to achieve the follow-up endpoint. Therefore, additional clinical manifestations that may have occurred after the follow-up could not be observed.…”
Section: Discussionmentioning
confidence: 99%